1998
DOI: 10.1080/00071669889358
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting direct and correlated responses in a White Leghorn population under long term selection for egg number

Abstract: 1. Data on 13,773 pullets, the progeny of 30 to 50 sires and about 135 to 220 dams per generation of a strain of White Leghorn under long-term selection for part period egg production over 16 generations, were examined. 2. Realised genetic gain per generation was highly significant for egg production (2.55 eggs), egg weight (-0.51 g), age at sexual maturity (-2.30 d) and 40 week body weight (-11.73 g). 3. The significant genetic response of 4.46 to 4.72 eggs per generation was realised in the first 8 generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Other factors such as small population size, inbreeding, drift change in fitness and/or approach to genetic/physiological limits might also influence the rate of response. The same conclusion was reported by (Quinton et al, 1992;Smith, 1995 andSharma et al, 1998). It was clear that EM2 showed a reduction per generation in spite of egg weight, this was probably due to the antagonism between body weight and egg number.…”
Section: Phenotypic and Genetic Changesupporting
confidence: 84%
“…Other factors such as small population size, inbreeding, drift change in fitness and/or approach to genetic/physiological limits might also influence the rate of response. The same conclusion was reported by (Quinton et al, 1992;Smith, 1995 andSharma et al, 1998). It was clear that EM2 showed a reduction per generation in spite of egg weight, this was probably due to the antagonism between body weight and egg number.…”
Section: Phenotypic and Genetic Changesupporting
confidence: 84%
“…In experimental lines not selected for egg production heritability of this trait may reach almost 0.5 (Anang et al, 2000a) whereas in commercial lines it is often less than 0.2 (Zięba, 1990;Preisinger and Savas, 1997). In long-term selection studies it was also shown that realised heritability may change over generations (Sharma et al, 1998). Low heritability estimates may result from a reduction in genetic variance due to selection but also from the overestimation of error variance due to the high skewness of traits.…”
Section: Methodsmentioning
confidence: 99%
“…A trend for increase in housing and mature body weight with selection for egg produetion plus egg weight probably due to the influence of egg size has been observed in most of the lines in such selection experiments (KOLSTAD, 1980;LILJEDAHL and WEYDE, 1980;SORENSEN et al, 1980). This is in contrast to the results of single-trait selection for egg produetion (AYYAGARI et al, 1983;SHARMA et al, 1998) in which housing and mature body weights showed a downward trend. The ratio of 40-to 20-week body weight did not change indicating that both the body weights were equally altered.…”
Section: Resultsmentioning
confidence: 92%
“…The economic gain in layer chickens depends on a number of mutually associated traits some of which are antagonistically correlated (FAIRFULL and GOWE, 1990). A number of selection experiments for increasing part-year egg produetion have yielded positive responses in egg number but also invariably produced concomitant reduction in egg weight (recent ones being those ofAYYAGARI et al., 1983;JORJANI et al, 1993;SHARMA et al, 1998). There are few reports of selection for the simultaneous improvement of egg produetion, egg weight and other traits in layer Stocks undergoing long-term selection with sufficiently large population sizes and/or a suitable control population (GOWE and FAIRFULL, 1985;JORJANI et al, 1993).…”
Section: Introductionmentioning
confidence: 99%